Strategi Pembelajaran pada Anak Berkebutuhan Khusus dalam Pendidikan Inklusi - Nila Ainu Ningrum (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Children with special needs have their own perspective in learning a subject. Therefore, this article aims to analyze learning strategies for special needs children, which require a separate strategy according to their individual needs. This research uses qualitative research with a library research approach. Library study is a method that collects information or data relevant to the research topic through documents. The data in this article were obtained through literature studies in the form of books and journals. This research found that: 1) For schools to be able to maintain and improve the implementation of inclusive schools that are already running for the realization of equitable education, 2) for parents who have students with special needs to pay more attention to the development of children both academically and non-academically, and 3) for the government to pay more attention to inclusive education programs. Because in essence education does not belong to those who can afford it, but education is the human right of every human being in the world.